"I am OK when you are with me" – Understanding the well-being and innovative behavior in the digitized workspace. Issue 5 (26th July 2021) - Karani, Anushree; Mehta, Swapnil Abhishek
Abstract : Purpose: The study aimed at understanding the relationship between supervisor and coworker support, psychological contract fulfillment, work engagement, well-being (different forms) and innovative behavior in the digitized workspace during the coronavirus disease 2019 (COVID-19) pandemic. Design/methodology/approach: Data were collected via a structured questionnaire through Google Docs from 239 respondents working in the sales department of the consumer durable industry through snowball sampling. Findings: Supervisor and coworker support was positively contributing to psychological contract fulfillment. Further, psychological contract fulfillment was positively contributing to work engagement. Along with innovative behavior, four forms of well-being, i.e. emotional, psychological, workspace and life were studied as outcome variables. Work engagement positively contributes to innovative behavior and well-being. Research limitations/implications: The study examined the relationship between various organizational variables in consumer durable industry. Future work should involve studying the effect in other industries and functional areas. Practical implications: The study examined how the supervisor and coworker act as an enabler in fulfilling the psychological contract in the digitized workspace. Organizations also understand the importance of work engagement in maintaining well-being and innovative behavior. Originality/value: The paper initiates the important debate on well-being and innovative behavior in the digitized workspace for the sales employees of the consumer durable industry.